High-performance polyurethane-metal adhesive and application

By using a combination of grafted phenoxy resin with a weight average molecular weight of 46000-60000 and acetal resin, the problem of decreasing bonding strength of polyurethane-metal adhesives under high temperature conditions is solved, efficient and stable bonding of polyurethane and metals is achieved, and the shelf life of the product is extended.

CN119842347APending Publication Date: 2025-04-18SHANGHAI TONTEE NEW MATERIAL TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510052318.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The bonding strength of existing polyurethane-metal adhesives decreases under high temperature conditions, which is prone to large-area degumming. The rapid gelation process puts higher requirements on the bonding efficiency of the adhesive, resulting in a shortened storage stability and shelf life.

Method used

The phenoxy resin grafted with methacrylic acid and/or hydroxypropyl methacrylate with a weight average molecular weight of 46,000-60,000 is used as the main component, and the bonding promoter is defined as a combination of γ-glycidyl ether oxypropyl trimethoxysilane and acetal resin. By combining a specific modified phenoxy resin and an adhesive promoter, high bonding strength and stability under a curing agent are achieved.

Benefits of technology

It realizes efficient bonding between polyurethane and metal, and the bonding effect is more stable under high temperature conditions, extends the shelf life of the product, and meets the application needs of long-term pre-baking and short gel time, significantly improving the performance of the adhesive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005240336230000071
    Figure BDA0005240336230000071
  • Figure BDA0005240336230000081
    Figure BDA0005240336230000081
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, in particular to a high-performance polyurethane-metal adhesive and application. The adhesive is prepared from the following raw materials in percentage by weight: 40-70% of modified phenoxy resin, 1-15% of adhesion promoter, 0.1-5% of filler and the balance of solvent. The phenoxy resin which is grafted with methacrylic acid and / or hydroxypropyl methacrylate and has the weight-average molecular weight of 46000-60000 is introduced, and can still play a role in bonding metal in a curing agent-free system, so that the adhesive has relatively good bonding strength, and meanwhile, the adhesive can be quickly subjected to a cross-linking reaction with a polyurethane elastomer in a vulcanization process, so that the adhesion strength of the adhesive is improved, and the service life of the adhesive is prolonged. And meanwhile, the bonding of the adhesive under the high-temperature condition is more stable, and the problems that the storage period of a traditional adhesive is short, a bonded product is prone to degumming, and polyurethane is difficult to bond in the rapid gelation process are perfectly solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to a high-performance polyurethane-metal adhesive and applications thereof. Background Art

[0002] At present, polyurethane elastomer and metal bonding products are widely used in the caster industry. They retain the hardness characteristics of metal and incorporate the wear resistance and high load-bearing capacity of polyurethane elastomer, which is very suitable for the needs of these application scenarios. Polyurethane-metal adhesives play a vital role in many fields such as factories, logistics, medical facilities and furniture manufacturing.

[0003] In order to enhance the structural strength of the adhesive layer, traditional polyurethane-metal adhesives often use a two-component system or add a latent curing agent to enhance the curing effect. However, this practice not only increases the complexity of construction operations, but also weakens storage stability and shortens the shelf life of the product. In practical applications, the product generates a lot of heat, especially the temperature of the bonding part will rise rapidly in a short period of time. Due to the thin adhesive layer, it is easy to gradually lose its effectiveness during the rapid rise in high temperature, which eventually leads to a decrease in the bonding strength between the metal or polyurethane elastomer, and even large-scale debonding occurs in the destructive test, affecting the bonding effect. At the same time, in recent years, caster manufacturers tend to use polyurethane elastomers with shorter gel time to speed up demoulding and improve production efficiency. However, the rapid gelation process greatly shortens the reaction time between the elastomer and the adhesive, which puts more stringent requirements on the bonding efficiency of the adhesive.

[0004] For example, Chinese patent CN104403621A discloses a high-efficiency metal adhesive with a wide range of applications, especially for alloys, and a wide temperature tolerance range; Chinese patent CN1626606A discloses an environmentally friendly adhesive for metal-plastic composite panels and a preparation method thereof, which is composed of a main agent and a curing agent, wherein the raw material ratio of the main agent is: 10-80 parts by weight of polyurethane with hydroxyl groups, 5-50 parts by weight of polyester with a molecular weight of 600-1500, and 5-30 parts by weight of filler. The prepared adhesive can tightly bond the metal and the plastic core layer together, has good elasticity and bonding force, and will not become brittle at minus 30°C. However, none of these existing technologies solve the above technical problems, which seriously affects the scope of application. Summary of the invention

[0005] In order to solve the problems in the prior art, the first aspect of the present invention provides a high-performance polyurethane-metal adhesive. The raw materials for preparing the adhesive include, by weight percentage: 40-70% modified phenoxy resin, 1-15% adhesion promoter, 0.1-5% filler, and solvent to make up the balance.

[0006] In a preferred embodiment, the raw materials for preparing the adhesive include, by weight percentage: 40-70% of modified phenoxy resin, 1-15% of adhesion promoter, 0.1-0.5% of filler, and the balance is made up of solvent.

[0007] In one embodiment, the modified phenoxy resin is a phenoxy resin grafted with methacrylic acid and / or hydroxypropyl methacrylate.

[0008] In one embodiment, the weight average molecular weight of the modified phenoxy resin is 46000-60000, which can be 46000, 47000, 48000, 49000, 50000, 53000, 55000, 58000, 60000. Preferably, the weight average molecular weight of the modified phenoxy resin is 53000.

[0009] In one embodiment, the raw materials for preparing the modified phenoxy resin include, by weight percentage: 20-30% phenoxy resin, 0.1-0.5% initiator, 2-8% modifier, and the balance is made up of organic solvent.

[0010] In one embodiment, the initiator includes at least one of benzoyl peroxide, dicumyl peroxide, azobisisobutyronitrile, and potassium persulfate. Preferably, the initiator is benzoyl peroxide.

[0011] In one embodiment, the modifying agent includes at least one of methacrylic acid and hydroxypropyl methacrylate.

[0012] In a preferred embodiment, the mass ratio of methacrylic acid to hydroxypropyl methacrylate is (0.5-2):(2.1-5.8), which may be 0.5:2.1, 0.5:2.2, 0.5:5.8, 2:2.1, 2:2.2, 2:5.8.

[0013] In one embodiment, the organic solvent includes at least one of cyclohexanone, acetone, butanone, and xylene. Preferably, the organic solvent is cyclohexanone.

[0014] In one embodiment, the preparation method of the modified phenoxy resin comprises: dissolving the phenoxy resin in an organic solvent, heating to 90° C., adding an initiator and a modifier, and reacting at the temperature for 3 hours to obtain the modified phenoxy resin.

[0015] In one embodiment, the adhesion promoter includes at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane.

[0016] In one embodiment, the adhesion promoter comprises an acetal resin.

[0017] In a preferred embodiment, the adhesion promoter is a combination of γ-glycidyloxypropyltrimethoxysilane and acetal resin.

[0018] In a preferred embodiment, the weight average molecular weight of the acetal resin is 50,000-60,000.

[0019] In a more preferred embodiment, the mass ratio of the γ-glycidyloxypropyltrimethoxysilane to the acetal resin is 2:1.

[0020] In one embodiment, the filler includes at least one of carbon black, silica, red iron, titanium dioxide, fly ash, and mica powder. Preferably, the filler is red iron.

[0021] In one embodiment, the solvent includes at least one of cyclohexanone, acetone, butanone, methyl isobutyl ketone, xylene, ethylbenzene, ethyl acetate, and dimethyl carbonate.

[0022] In a preferred embodiment, the solvent is a combination of methyl isobutyl ketone, xylene and dimethyl carbonate.

[0023] In a more preferred embodiment, the mass ratio of xylene, methyl isobutyl ketone and dimethyl carbonate is (10-20): (8-15): (5-10). More preferably, the mass ratio of xylene, methyl isobutyl ketone and dimethyl carbonate is 15:11:7.7.

[0024] In one embodiment, the preparation method of the high-performance polyurethane-metal adhesive comprises: stirring and evenly dispersing a modified phenoxy resin, an adhesion promoter, a filler and a solvent to obtain the high-performance polyurethane-metal adhesive.

[0025] The second invention of the present invention provides an application of a high-performance polyurethane-metal adhesive in polyurethane-metal products.

[0026] Beneficial Effects

[0027] 1. The present invention introduces a phenoxy resin grafted with methacrylic acid and / or hydroxypropyl methacrylate with a weight average molecular weight of 46,000-60,000, which can still play the role of bonding metal in a curing agent-free system, so that the adhesive has good bonding strength. At the same time, it can quickly undergo a cross-linking reaction with the polyurethane elastomer during the vulcanization process, thereby achieving bonding between polyurethane and metal, and at the same time making the bonding of the adhesive more stable under high temperature conditions.

[0028] 2. The present invention limits the adhesion promoter to γ-glycidyloxypropyltrimethoxysilane and acetal resin, and further controls the mass ratio of the two to 2:1, so that it has good mechanical properties and further improves the stability of the system.

[0029] 3. Compared with traditional adhesives, the high-performance polyurethane-metal adhesive prepared by the present invention innovatively adopts a specific modified phenoxy resin, and has higher bonding strength without adding a curing agent and a catalyst, which perfectly solves the problems of short storage period of traditional adhesives, easy degumming of bonded products, and difficulty in bonding polyurethane during rapid gelation.

[0030] 4. The high-performance polyurethane-metal adhesive provided by the present invention can meet the downstream industry's demand for long-term pre-baking (up to 120°C for 24 hours) and short gel time (1-2 minutes) polyurethane elastomers, and there is no obvious performance degradation in the applications with the above special requirements. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The experimental methods in the examples without specifying specific conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.

[0032] Example 1

[0033] The first aspect of the present embodiment provides a high-performance polyurethane-metal adhesive. The raw materials for preparing the adhesive include, by weight percentage: 57% modified phenoxy resin, 9% adhesion promoter, 0.3% filler, and 33.7% solvent.

[0034] The modified phenoxy resin is a phenoxy resin grafted with methacrylic acid and hydroxypropyl methacrylate.

[0035] The weight average molecular weight of the modified phenoxy resin is 53,000.

[0036] In terms of weight percentage, the raw materials for preparing the modified phenoxy resin include: 27% phenoxy resin, 0.2% initiator, 2.7% modifier, and the balance is made up of organic solvent.

[0037] The phenoxy resin is of Huntsman PKHH brand, purchased from Dongguan Haosheng Plastic Raw Materials Co., Ltd.

[0038] The initiator is benzoyl peroxide.

[0039] The modifiers are methacrylic acid and hydroxypropyl methacrylate, and the mass ratio of methacrylic acid to hydroxypropyl methacrylate is 0.5:2.2.

[0040] The organic solvent is cyclohexanone.

[0041] The preparation method of the modified phenoxy resin comprises: dissolving the phenoxy resin in an organic solvent, heating the temperature to 90° C., adding an initiator and a modifier, and reacting the mixture for 3 hours to obtain the modified phenoxy resin.

[0042] The adhesion promoter is a combination of γ-glycidyloxypropyltrimethoxysilane and acetal resin, and the mass ratio of the γ-glycidyloxypropyltrimethoxysilane to the acetal resin is 2:1.

[0043] The acetal resin has a brand number of BA55HH and is purchased from Kuraray of Japan.

[0044] The filler is iron red.

[0045] The solvent is a combination of methyl isobutyl ketone, xylene and dimethyl carbonate, wherein the mass ratio of xylene, methyl isobutyl ketone and dimethyl carbonate is 15:11:7.7.

[0046] The preparation method of the high-performance polyurethane-metal adhesive comprises: stirring and evenly dispersing the modified phenoxy resin, the adhesion promoter, the filler and the solvent to obtain the adhesive.

[0047] A second aspect of this embodiment provides an application of a high-performance polyurethane-metal adhesive in a polyurethane-metal product.

[0048] Example 2

[0049] The specific implementation of this embodiment is the same as that of Example 1, except that the raw materials for preparing the modified phenoxy resin in this embodiment include, by weight percentage, 27% phenoxy resin, 0.4% initiator, 2.6% modifier, and the balance made up by organic solvent.

[0050] The adhesion promoter is γ-glycidyloxypropyltrimethoxysilane.

[0051] Example 3

[0052] The specific implementation of this embodiment is the same as that of Example 1, except that the raw materials for preparing the modified phenoxy resin described in this embodiment include, by weight percentage, 22% phenoxy resin, 0.2% initiator, 7.8% modifier, and the balance made up by organic solvent.

[0053] Comparative Example 1

[0054] The specific implementation of this comparative example is the same as that of Example 1, except that the adhesion promoter in this comparative example is γ-glycidyloxypropyltrimethoxysilane.

[0055] Comparative Example 2

[0056] The specific implementation of this comparative example is the same as that of Example 1, except that the raw materials for preparing the modified phenoxy resin in this comparative example include, by weight percentage, 27% phenoxy resin, 0.4% initiator, 2.6% modifier, and the balance made up by organic solvent.

[0057] The adhesion promoter is γ-glycidyloxypropyltrimethoxysilane.

[0058] Comparative Example 3

[0059] The specific implementation of this comparative example is the same as that of Example 1, except that the brand of the phenoxy resin in this comparative example is Huntsman PKHB, which is purchased from Dongguan Haosheng Plastic Raw Materials Co., Ltd.

[0060] The weight average molecular weight of the modified phenoxy resin is 30,000.

[0061] Comparative Example 4

[0062] The specific implementation of this comparative example is the same as that of Example 1, except that the brand of the phenoxy resin in this comparative example is Huntsman PKHC, which is purchased from Dongguan Haosheng Plastic Raw Materials Co., Ltd.

[0063] The weight average molecular weight of the modified phenoxy resin is 40,000.

[0064] Comparative Example 5

[0065] The specific implementation of this comparative example is the same as that of Example 1, except that the brand of the phenoxy resin in this comparative example is Huntsman PKFE, which is purchased from Dongguan Haosheng Plastic Raw Materials Co., Ltd.

[0066] The weight average molecular weight of the modified phenoxy resin is 65,000.

[0067] Performance Testing

[0068] 1. Conventional pressure-release test:

[0069] A Φ26 carbon steel ring was used, and the adhesive prepared in Examples 1-3 and Comparative Examples 1-5 was evenly coated on the outside of the ring, and commercially available adhesive samples Thixon 422 and CILBOND 49SFC were compared in parallel, and the dry film thickness of the adhesive was controlled at 20 μm. After sufficient drying, a blast drying oven was used, and the carbon steel ring was pre-cured at 100°C for 2 hours at a fixed temperature, and then the carbon steel ring was placed in a mold, and a polyurethane elastomer (D3249 purchased from Shandong Yinuowei) was poured, and a first stage vulcanization was performed at 120°C for 1 hour, and a second stage vulcanization was performed at 100°C for 12 hours after demolding, and the test sample was obtained after cooling to room temperature, and the carbon steel ring was pressurized and separated from the polyurethane for conventional compression test.

[0070] 2. Thermal shock test: After keeping the temperature at 80℃ for 1h, press and release in a high temperature test chamber at a constant temperature of 80℃.

[0071] 3. Water boiling resistance test: Boil in a constant pressure water bath at 70℃ for 72h to separate the carbon steel ring and polyurethane under pressure.

[0072] 4. Salt spray resistance test: After being placed in a 5% NaCl fog machine at 35°C for 480 hours, the carbon steel ring and the polyurethane are separated under pressure.

[0073] 5. Heat aging test: After the glue is stored at 50℃ for 42 days, the adhesion is tested and it is directly pressed off.

[0074] The above tests 2-5 used the same sample preparation method as test 1, and the test results are shown in Table 1.

[0075] It can be seen from Table 1 that the high-performance polyurethane-metal adhesives prepared in Examples 1-3 are similar to or even better than commercially available brands in terms of maximum peel load and adhesive attachment rate.

[0076] Table 1

[0077]

[0078] 6. Long-term pre-baking pressure-release test: The test process is the same as the conventional pressure-release test process above, except that the pre-curing condition is extended from 100℃2h to 120℃24h. The test results are shown in Table 2.

[0079] 7. Rotational viscosity and dry film thickness test: Paste a layer of 3M tape on the carbon steel ring, ensure that the tape fits tightly to the ring without bubbles, then apply 15-30μm thick adhesive on the tape, remove the tape after it is completely dry, and use a film thickness meter to test the thickness of the adhesive layer on the tape. The test results are shown in Table 2.

[0080] 8. Short gel time polyurethane pressure release test: Use a Φ26 carbon steel ring, and evenly coat the adhesive prepared in Examples 1-3 and Comparative Examples 1-5 on the outside of the ring, and compare the commercially available adhesive samples Thixon 422 and CILBOND49SFC in parallel. The dry film thickness of the adhesive is controlled at 20μm. After sufficient drying, use a blast drying oven, keep the temperature constant at a fixed temperature, pre-cure the carbon steel ring at 100°C for 2h, then put the carbon steel ring into the mold, use MDI type prepolymer (YK3085 purchased from Zhejiang Youke), mix with 1,4-butanediol and catalyst (CUCAT-US from Guangdong Yourun) (the catalyst dosage is 0.5wt% of 1,4-butanediol), quickly pour within 30s, vulcanize at 120°C for 15min, and vulcanize at 100°C for 16h after demoulding. After cooling to room temperature, the carbon steel ring is separated from the polyurethane by pressure. The test results are shown in Table 2.

[0081] 9. Fatigue test: Use 6-inch wheel core, size 58mm×77mm, pre-curing condition 100℃2h, first stage vulcanization condition 120℃1h, second stage vulcanization condition 100℃12h after demoulding, test conditions are load 600kg, speed 6km / h, record the mileage and adhesive rate of the final product after destruction, test results are shown in Table 2. / in the table means that this test was not conducted.

[0082] Table 2

[0083]

[0084] From the data in Table 2, we can see that:

[0085] 1) Except for the fact that Thixon 422 is not resistant to long-term heating due to system reasons, the high-performance polyurethane-metal adhesive of the present invention has similar maximum peel load and adhesive attachment rate to those of traditional brands under long-term pre-baking conditions, and has no obvious attenuation compared with the conventional pressure-release test results, indicating that the high-performance polyurethane-metal adhesive prepared by the present invention has excellent thermal stability;

[0086] 2) When the high-performance polyurethane-metal adhesive of the present invention is bonded to a polyurethane elastomer with a short gel time, the maximum peel load is similar to that of commercial brands, the adhesive rate is better than that of commercial brands, and the proportion of RC failure is much smaller than that of commercial brands, which further proves that the reaction rate between the prepolymer with a short gel time is higher, and the attenuation is obviously small compared with the compression test results;

[0087] 3) The high-performance polyurethane-metal adhesive of the present invention has a driving mileage and adhesive rate similar to those of conventional commercially available brands when bonding products. The present invention can effectively improve the bonding strength between polyurethane elastomers and metals, and can better resist high temperatures during application, thereby forming a better bonding effect;

[0088] 4) The molecular weight of the modified phenoxy resin directly determines the viscosity and dry film thickness of the adhesive. When the molecular weight is too low, the film thickness becomes thinner, resulting in the inability to achieve good bonding strength for both the prepolymer and the substrate; when the molecular weight is too high, the film thickness is too thick, resulting in reduced dry film strength, unable to withstand the modulus difference between the prepolymer and the substrate, resulting in faster failure and lower adhesive attachment rate.

Claims

1. A high-performance polyurethane-metal adhesive, characterized in that: Calculated by weight percentage, the raw materials for preparing the adhesive include: 40-70% of modified phenoxy resin, 1-15% of adhesion promoter, 0.1-5% of filler, and the balance is made up of solvent.

2. The high performance polyurethane-metal adhesive according to claim 1, characterized in that: The modified phenoxy resin is a phenoxy resin grafted with methacrylic acid and / or hydroxypropyl methacrylate.

3. The high performance polyurethane-metal adhesive according to claim 1 or 2, characterized in that: The weight average molecular weight of the modified phenoxy resin is 46000-60000.

4. The high performance polyurethane-metal adhesive according to claim 1, characterized in that: The raw materials for preparing the modified phenoxy resin include, by weight percentage, phenoxy resin 20-30%, initiator 0.1-0.5%, modifier 2-8%, and organic solvent making up the balance.

5. The high performance polyurethane-metal adhesive according to claim 4, characterized in that: The initiator includes at least one of benzoyl peroxide, dicumyl peroxide, azobisisobutyronitrile and potassium persulfate.

6. The high performance polyurethane-metal adhesive according to claim 1, characterized in that: The adhesion promoter includes at least one of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, and γ-methacryloxypropyl trimethoxysilane.

7. The high performance polyurethane-metal adhesive according to claim 1, characterized in that: The adhesion promoter includes an acetal resin.

8. The high performance polyurethane-metal adhesive according to claim 1, characterized in that: The filler includes at least one of carbon black, silica fume, red iron oxide, titanium dioxide, fly ash and mica powder.

9. The high performance polyurethane-metal adhesive according to claim 1, characterized in that: The solvent includes at least one of cyclohexanone, acetone, butanone, methyl isobutyl ketone, xylene, ethylbenzene, ethyl acetate, and dimethyl carbonate.

10. An application of the high-performance polyurethane-metal adhesive according to any one of claims 1 to 9, characterized in that: Used in polyurethane-metal products.

Citation Information

Patent Citations

  • Efficient metal adhesive

    CN104403621A

  • Environmental protection type adhesive in use for composite board of metal and plastic and preparation method

    CN1626606A